HEEP (Hybrid Energy Efficiency Protocol) based on chain clustering. (27th June 2011) - Boubiche, Djallel Eddine; Bilami, Azeddine
Wireless Sensor Networks have emerged as a new information-gathering system based on the collaborative efforts of large number of tiny sensors with limited resource. Energy constraints distinguish sensors networks from other wireless communication networks. Energy efficiency and network lifetime have been the focus of many research works on sensor networks, such as energy aware routing. This paper suggests a new routing protocol called HEEP which combines two algorithms: LEACH and PEGASIS. HEEP advise a new network self-organisation approach, that join clusters-based and the chain-based approaches. This new approach is called chains clustering approach. Organising the network nodes in chains clusters avoids the bad energy dissipation in LEACH protocol and reduces the routing delay generated by PEGASIS protocol. The experimental results show that HEEP outperforms LEACH and LEACH-C with more 110% of network lifetime, and reduces the routing delay introduced in PEGASIS by 50%.